Steiner's hat : a constant-area deltoid associated with the ellipse - Garcia, Ronaldo (Array, 2020)
The Negative Pedal Curve (NPC) of the Ellipse with respect to a boundary point M is a 3-cusp closed-curve which is the affine image of the Steiner Deltoid. Over all M the family has invariant area and displays an array of interesting properties.